Continuous microreactor synthesis of ZIF-8 with high space-time-yield and tunable particle size - Polyzoidis, Angelos; Altenburg, T.; Schwarzer, Maud; Loebbecke, S.; Kaskel, Stefan (Chemical Engineering Journal, 2016)
The continuous synthesis of the metal-organic framework ZIF-8 is described, employing microreaction technology which provides highly controlled mass and heat transport conditions. Using a T-type micromixer connected with a residence time capillary, crystalline ZIF-8 with excellent product characteristics and remarkable reproducibility is produced within seconds. The product is obtained at production rates of up to 640g/day which corresponds to a theoretical space-time yield of 210,000kg/m3*day. The modular process setup allows easy scale-up into the several kilogram range. Additionally, by modifying the reaction and process conditions it is possible to intentionally tailor both, the microscopic (crystal form and size) and macroscopic morphology of the product.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Continuous synthesis; Metal-organic frameworks; Microreaction technology; ZIF-8